Orthopedic Providers' Preferences for Education and Training on Psychosocial Clinical Research Initiatives: A Qualitative Investigation. (April 2022) - Sagar, Isabell; Popok, Paula J.; Reichman, Mira; Lester, Ethan G.; Doorley, James; Bakhshaie, Jafar; Vranceanu, Ana Maria
Introduction: Psychosocial factors (e.g., depression, anxiety) increase risk for chronic pain, disability, and other health complications following acute orthopedic traumatic injury. Orthopedic providers lack skills to address these factors. Education around psychosocial factors of recovery and psychosocial clinical and research initiatives could address this gap. The purpose of this study was to understand orthopedic trauma providers' preferences for the design and distribution of educational materials to facilitate psychosocial initiative implementation. Methods: We conducted live-video, semi-structured focus groups with outpatient orthopedic trauma providers across three Level 1 Trauma Centers, using a hybrid inductive-deductive approach to analyze qualitative data and extract themes and subthemes characterizing providers' recommendations for appropriate psychosocial education. Results: Four themes described providers' recommendations for receiving educational materials: (1) provide foundational knowledge and tools about psychosocial factors; (2) provide information regarding a psychosocial initiative's purpose and procedures; (3) leverage educational materials to maximize buy-in to psychosocial clinical research initiatives; and (4) deliver information concisely, clearly, and electronically. Conclusion: Orthopedic providers recommended ways to optimize design and dissemination of education on psychosocial care. Optimizing knowledge of psychosocial factors and clinical and research initiatives facilitates providers' ability to appropriately target the often-underdressed psychosocial component of recovery in orthopedics.